Sosialisasi Pentingnya Menjaga Kesehatan Gigi dan Mulut di UPTD SDN 4 Nagrikaler Purwakarta - Ai Saaadah; Annisa Hertanty; Femi Githa Maulina; Indah Thania Kusumah; Maria Firda Agustine; Ranika Yuliasari (Jurnal Pengabdian Masyarakat PGSD, 2021)
The community service program carried out is one of the mandatory activities in the Introduction to Education Unit Field course. This service activity is carried out by making a socialization activity so that the benefits of the activity can be directly received by the target of the activity. The purpose of this activity is to socialize the importance of maintaining oral health in elementary school environment as a form of concern regarding the health of students' teeth and mouth. The method of socializing this community service program is executed online using the Zoom application with presenters and offline with students. The location of the socialization of this service program was carried out at the elementary educational technical implementation unit of SD Negeri 4 Nagrikaler, Purwakarta district, West Java province. The target of this activity program is lower-grade students, more precisely students who are currently studying at the 2nd grade elementary school level. The result of the socialization of the community service program that has been implemented is the increased knowledge and awareness of students about the importance of maintaining the health of their teeth and mouth.